The Presence of Earnings Manipulation Incentives as a Prerequisite for the Benefits of Higher-Quality Audit to be Realized: The Case of Indonesia - ARIE RAHAYU HARIANI; Zaki Baridwan (The Indonesian Journal of Accounting Research, 2013)
This paper examines the interaction between the incentives that drives earnings manipulation and the audit practice that deters it. Accountants tend to overlook earnings manipulation incentives while overemphasizing audit quality. This notion is verified from public auditors' predisposition to prescribe restrictive standards to enhance audit quality every time a financial scandal occurs. Evidence supports our hypotheses that the benefits of higher-quality audit could be realized only if the earnings manipulation exists at the first place. Incentives for conducting earnings management are demonstrated to be a strong predictor in determining the occurrences or attempts to engage in earnings manipulation. Earnings management incentives can also be determined before the audit is conducted.